A peep into an African kitchen : perspectives of Onitsha, Nigeria - Egbuna, Ngozi (Enugu, Nigeria : Delta Publications (Nigeria) Limited, 2005)
The book records and highlights some basic values and cultural significance of the African cuisine from the perspectives of native food customs of Onitsha people of South-Eastern Nigeria.
Includes bibliographical references and index.
oif 28/02/17
Loans
Keywords: Cooking, Nigerian; Cooking; Manners and customs; Onitsha (Nigeria) -- Social life and customs; Onitsha (Nigeria)